Los fantasmas del Quijote - Mariarosa Scaramuzza Vidoni (Mélanges de la Casa de Velázquez)
Beginning in the 1960s, different readings of Cervantes’ master-work began to appear, penned by illustrious French personalities in the human sciences, and in particular in the fields of psychoanalysis and anthropology: Michel Foucault, Marthe Robert and René Girard. Most of these interpretations have focused on Don Quixote the character rather than Don Quixote the novel – on the hero’s ghosts rather than on the novel as an artistic construct. Louis Combet attempted a preliminary synthesis of some of the results of this research using procedures typical of literary Hispanism, thus paving the way for new insights.